Madagascar Economic Update, March 2011 : Aid Effectiveness during Political Instability - A Look at Social Sectors - World Bank (Washington, DC, 2017)
In Madagascar, donors have traditionally counted for almost half of the government's budget and have been, by far, the main source of funding in social sectors. Since the beginning of the crisis, official aid toward education, health, and social protection surged, reaching almost US$260 million in 2010 against US$180 million in 2008. This increased failed nonetheless to improve significantly social indicators. Official aid flows have been cut since beginning of the political crisis except to social sectors where donors have increased significantly their disbursements between 2008 and 2010. This increase has been justified on humanitarian grounds, to respond to the growing social distress of the population. Unfortunately, most social indicators have continued to fall, as evidenced by the recent drop in net registration rate in primary schools, the rate of births attended by medical staff, and the use of external medical consultations.